Color and cognitive penetrability - Zeimbekis, John (Philosophical studies, 2013)
Several psychological experiments have suggested that concepts can influence perceived color (e. g., Delk and Fillenbaum in Am J Psychol 78(2):290-293, 1965, Hansen et al. in Nat Neurosa 9(11):1367-1368, 2006, Olkkonen et al. in J Vis 8(5):1-16, 2008). Observers tend to assign typical colors to objects even when the objects do not have those colors. Recently, these findings were used to argue that perceptual experience is cognitively penetrable (Macpherson 2012). This interpretation of the experiments has far-reaching consequences: it implies that the way we think of objects determines how we see them, thus threatening the role of perception in justifying beliefs. In this paper, I show that the psychological findings can be accounted for without admitting cognitive penetrability. An underestimated but key feature of the experiments is that observers had to judge colors in borderline cases, in conditions of reduced acuity, or on the basis of color-concepts instead of matching. Such judgments are sensitive to the form of bias that Tversky and Kahneman (Science 185: 1124-1131, 1974) have termed 'anchoring'. Adopting a suggestion from Raffman (Philos Rev 103(1): 41—74, 1994), I argue that the way subjects in the experiments think of the objects could affect their color judgments without altering their color experiences.